A inserção de povos originários em áreas urbanas: Javaé na cidade de Formoso do Araguaia -TO - Oliveira, Vanilza Gonçalves de (2024)
The history of original peoples involves the idea of resistance against those who took over their habitat. In this view, the research is justified because it is essential to debate the spaces in political-cultural conflict that have expanded due to the driving force of greed in defending socioeconomic development for the regions without addressing the realities of the people. From this perspective, the question that guides the study is in what aspects can the culture of the Javaé people be visible in the Tocantins region? The central objective is to investigate the Javaé people regarding the occupation and formation of the municipality of Formoso do Araguaia. The specific objectives aim to characterize Bananal Island with its history, portray the municipality of Formoso do Araguaia with its projects, verify the participation of the Javaé ethnic group in the formation of the society of Formoso do Araguaia, address the representations of the Javaé in the regional context in the face of invisibilization of their culture, point out the methodological procedures and expose the participants' reports with their profile and cultural visibility. The methodology has a qualitative character, whose bibliographical review and fieldwork with the reports of seven participants from the Javaé people are considered as sources, with the methodological procedure together with the bibliographical review and the ethnographic model for the descriptive record of the culture of the Javaé people. The semi-structured interviews were carried out in Formoso do Araguaia, state of Tocantins, from the 16th to the 19th of January 2024. The historiographical data of these people show the institutions and government policies that marked the territorial issue as an ancient phenomenon, this subject being always current. In the results, the colonizers bias significantly impacted the history, territorial occupation and culture of the indigenous people. The conflicts were supported by state laws, prevailing government projects that imposed their will in spaces previously occupied only by original groups